Decrease of Functioning in Remitted and Non-Remitted Patients 16 Years After a First-Episode Schizophrenia. Issue 6 (June 2015) - Marchesi, Carlo; Affaticati, Andrea; Monici, Alberto; De Panfilis, Chiara; Ossola, Paolo; Ottoni, Rebecca; Tonna, Matteo
Abstract : Abstract: In schizophrenia, a better level of functioning has been generally associated with symptomatic remission. However, this association has been supported by cross-sectional studies or by studies with a short follow-up period. Forty-eight patients with schizophrenia were evaluated by the Positive and Negative Symptoms Scale and the Social and Occupational Functioning Assessment Scale (SOFAS) at the first episode and after a mean period of 16 years. At follow-up, patients were defined as remitters (R) or non-remitters (NR) according to the Remission Schizophrenia Working Group criteria. R ( n = 18; 37.5%) compared to NR showed at the first episode a lower illness severity and a better level of functioning. A functional decline was found in both groups at follow-up, even though NR showed a more than twofold reduction than R. Better SOFAS scores at follow-up were predicted by baseline SOFAS score and less severe negative symptoms at follow-up. Schizophrenia implies a functional decline over time, regardless of the symptomatic remission status with negative symptoms playing a major role.